EFEKTIVITAS PENERAPAN PRENATAL YOGA DALAM MENINGKATKAN KUALITAS TIDUR PADA IBU HAMIL TRIMESTER KETIGA - Febrina Putri, Cyntia Hemas; Ganisia, Ainun; Rakhmalia Imeldawati (Jurnal Medicare, 2026)
Sleep disturbances are common in third-trimester pregnancy due to discomfort and anxiety, potentially harming maternal and fetal health. This study aims to determine if prenatal yoga improves sleep quality. A case study was conducted on a pregnant woman in the third trimester in Surabaya from January to April 2025. Data were collected using interviews, observations, and the Pittsburgh Sleep Quality Index (PSQI) before and after intervention. Prenatal yoga was delivered 4 times over 1 month, lasting 30-60 minutes per session. Results showed a decrease in PSQI score from 16 (poor) to 5 (good) after yoga. It is concluded that prenatal yoga improves sleep quality through relaxation and flexibility. Regular prenatal yoga is recommended to maintain fitness and rest before delivery.